Penerapan Metode Role Playing Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di Kelas V SD N 1 Prigi Banjarnegara - Lisa Kinanti,; Faisal Kamal; Pamungkas Stiya Mulyani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is motivated by the problem in Indonesia where many generations in the world of education still do not understand the content of the material because many educators still use monotonous methods without two-way communication and this results in a lack of students' understanding of the learning material. The role playing method is one solution that can boost various aspects of students, both cognitive, psychomotor and affective, which can be implemented in everyday life so that the nation's next generation becomes a generation that is powerful, knowledgeable and efficient. This research aims to determine the application of the Role Playing method in improving student learning outcomes in PAI subjects. The research method used is quantitative research methods. The results of the research show that the application of the role playing method in improving student learning outcomes in Islamic Religious Education subjects in class V of SD Negeri 1 Prigi, Sigaluh District, Banjarnegara Regency after using the role playing method can improve. This is proven by the students' learning results before taking action or using the role playing method which only reached an average score of 61.72 with classical completeness of 32%. After taking action in cycle I by applying the role playing method, student learning outcomes increased to an average score of 70.72 with classical completeness of 60%. Then in cycle II, using the role playing method, student learning outcomes also increased with an average score of 83.76 and students' classical completeness was 96%. Therefore, it is said to be effective in increasing learning outcomes because the success indicator that has been set is more than 76%.